Weight stigma, coping strategies, and mental health among children with overweight - Chung-Ying Lin (Wolters Kluwer Medknow Publications, 2019)
Introduction: Obesity/overweight (hereafter, overweight indicates both obesity and overweight) is an important health issue that is gaining growing interest worldwide. One health issue for children with overweight is stigma. The aims of this study were (1) to detect the impact of stigma on mental health and (2) to probe the effects of positive and negative coping on the mental health of children with overweight. Methods: The author conducted a secondary data analysis using two waves of data from the Taiwan Education Panel Survey (TEPS): the first wave in 2001 and the second wave in 2003. A group of junior high school students (in the 7th grade in the first wave; n = 2612; nmale = 1171) was used for data analysis. Items in the TEPS were categorized into the following five variables: mental health (nine items), stigma from peers (three items in relationship with peers and four items in bullying experience), stigma from parents (four items), positive coping strategies (six items in increasing social activities and two items in increasing self-study activities), and negative coping strategies (five items). Results: The overweight group experienced more peer stigma than the normal-weight group. Bullying experience, stigma from parents, and self-study activities were significantly correlated to mental health in both groups. The overweight group demonstrated stronger negative relationships between bullying events, negative strategies, and mental health than the normal-weight group; a weaker negative relationship was shown between stigma from parents and mental health. Conclusion: Stigma and negative strategies could endanger mental health among children with overweight.